Usage of Surfactant and Evaluation of Lung Problems in Late Preterm Infants - Ozlem Yilman; Senem Alkan Ozdemir; Sebnem Calkavur; Tulin Gokmen Yildirim (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: We aimed to evaluate surfactant frequency and surfactant indications, as well as lung problems in late preterm infants.